CANCER IMMUNOLOGY AND IMMUNOTHERAPY - UNDERSTANDING AND ADAPTATION THE CURRENT EVIDENCE TO OPTIMIZE PATIENT THERAPY OUTCOMES. - Orlin Savov; Vladimir Mladenov; Mitko Tzvetkov; Dimitar Mladenov (Peytchinski Publishing, 2015)
The aim of this publication includes the try to act as intermediary to the readers, which should be able to understand: - The description of the cancer immunotherapy mechanisms in the context of current therapy decisions for the treatment of cancer - The including criteria for those patients with cancer who could be appropriate candidates for immunotherapy - And to optimize patient outcomes by using best practices to manage the adverse events associated with immunotherapy treatment More than 15 promising immunotherapy approaches being tested in clinical trials with appropriate patients and colleagues for enrollment and peer-to-peer education purposes, respectively.